Mental health in post-earthquake Nepal - Thapa, Kiran (Nepal Journal of Epidemiology, 2015)
For two decades, Government of Nepal has made efforts to develop and maintain mental health professionals in all areas; however, much has to be done. This could be an opportunity for Nepal to redesign mental healthcare services at the community level. Primary mental health services integrated with community mental health could help children and families cope with and recover from mental illnesses in the long run.